Nd3+, Ho3+-Codoped apatite-related NaLa9(GeO4)6O2 phosphors for the near- and middle-infrared region. Issue 39 (20th September 2018) - Baklanova, Yana V.; Lipina, Olga A.; Enyashin, Andrey N.; Surat, Ludmila L.; Tyutyunnik, Alexander P.; Tarakina, Nadezda V.; Fortes, A. Dominic; Chufarov, Alexander Yu.; Gorbatov, Evgeny V.; Zubkov, Vladimir G.
Abstract : The apatite-like NaLa9 (GeO4 )6 O2 :Nd 3+, Ho 3+ phosphor is prepared using the solid-state method. Abstract : The apatite-like NaLa9 (GeO4 )6 O2 :Nd 3+, Ho 3+ phosphor is prepared using the solid-state method. Rietveld refinement of high-resolution time-of-flight neutron powder diffraction measurements indicate that this compound crystallizes in the hexagonal system with space group P 63 / m, Z = 1 and unit cell parameters a = 9.88903(6) Å, c = 7.25602(5) Å, V = 614.521(7) Å 3 at room temperature. The 4f sites are statistically occupied by La, Nd and Na, while 6h sites are occupied by La and Nd. Luminescence in the near- and middle-IR range caused by the transitions in neodymium and holmium ions is excited under 808 nm laser diode radiation. The highest emission intensity in NaLa9− x − y Nd x Ho y (GeO4 )6 O2 is attained at trace amounts of holmium, and it decreases sharply when y increases to 0.01. The IR phosphors have a good thermal stability and exhibit a very weak upconversion emission in the red spectral range upon 808 nm excitation. A scheme of excitation and emission pathways involving ground/excited state absorption, energy transfer, cross-relaxation, nonradiative multiphonon relaxation processes in Nd 3+ and Ho 3+ ions has been proposed. The data analysis indicates that Nd 3+ ions serve as sensitizers for Ho 3+ ions in these compounds, stimulating intense 2.1 μm and 2.7 μm emissions. These apatite-related germanate phosphors are promising materials for near- and middle-infrared solid-state lighting applications.